Secure data management 9th VLDB Workshop, SDM 2012, Istanbul, Turkey, August 27, 2012, proceedings - SDM (Workshop) (Lecture notes in computer science, 2012)
This book constitutes the refereed proceedings of the 9th VLDB Workshop on Secure Data Management held in Istanbul, Turkey, in August 27, 2012. The 12 revised full papers presented were carefully reviewed and selected from 22 submissions. The papers are organized in topical sections on privacy protection, access control, secure storage on the cloud, and trust on the Web. Tradeoff analysis of relational database storage of privacy preferences. Differential privacy in practice. A model for quantifying information leakage -- Privacy protocol for linking distributed medical data.  Cloud and the city: facilitating flexible access control over data-streams -- Policies for composed emergencies in support of disaster management -- Indexing encrypted documents for supporting efficient keyword search.  Secure quasi-realtime collaborative editing over low-cost storage services -- Secure metric-based index for similarity cloud -- Provenance for web 2.0 data -- Towards enabling behavioral trust among participating cloud forensic data center agencies -- Towards trustworthy health platform cloud. Differential privacy in practice.  A model for quantifying information leakage -- Privacy protocol for linking distributed medical data. Cloud and the city: facilitating flexible access control over data-streams -- Policies for composed emergencies in support of disaster management -- Indexing encrypted documents for supporting efficient keyword search. Secure quasi-realtime collaborative editing over low-cost storage services -- Secure metric-based Iidex for similarity cloud -- Provenance for web 2.0 data -- Towards enabling behavioral trust among participating cloud forensic data center agencies -- Towards trustworthy health platform cloud.